KONTRAK PERSEROAN TERBATAS YANG MENGANDUNG TINDAKAN ULTRA VIRES - Bello, Yoel; Makkawaru, Zulkifli; Hamid, Abd. Haris (Postgraduate Bosowa University Publishing, 2021)
Kegiatas usaha perseroan terbatas dilaksanakan oleh organ perseroan terbatas yaitu Direksi perseroan terbatas, Direksi dapat mewakili perseroan terbatas untuk melakukan kontrak dengan pihak terkait. Tindakan mewakili Perseroan Terbatas oleh Direksi harus sesuai dengan aturan sebagaiman dalam Undang-Undang No. 40 Tahun 2007 Tentang Perseroan Terbatas atau yang telah ditentukan dalam Anggaran Dasar Perseroan Terbatas. Apabilan tidakan Direksi Perseroan Terbatas melaksanakan Kontrak yang dapat merugikan Perseroan karena bertentangan dengan Undang-Undang No. 40 Tahun 2007 Tentang Perseroan Terbatas atau yang telah ditatur dalam Anggaran Dasar Perseroan Terbatas maka kontrak yang dibuat mengandung Ultra Vires. Jika Direksi melakukan tindakan Ultra Vires maka sesuai dengan Pasal 61 Undang-Undang No. 40 Tahun 2007 tentang Perseroan Terbatas, kepada Pemegang sahan berhak mengajukan Gugatan terhadap Perseroan ke Pengadilan Negeri. Limited liability companies are carried out by Directors of limited liability companies. The directors can represent limited liability companies to enter into contracts with related parties. The act of representing a Limited Liability Company by the Board of Directors must be in accordance with the provisions in Law No. 40 of 2007 concerning Limited Liability Companies or those stipulated in the Articles of Association of Limited Liability Companies. If the actions of the Board of Directors of a Limited Liability Company implement a Contract that could be detrimental to the Company because it is contrary to Law No. 40 of 2007 concerning Limited Liability Companies or those stipulated in the Articles of Association of Limited Liability Companies, the contracts made contain Ultra Vires. If the Board of Directors carries out Ultra Vires actions, in accordance with Article 61 of Law No. 40 of 2007 concerning Limited Liability Companies, the shareholders have the right to file a lawsuit against the Company to the District Court.